The APPEESFRS peptide, restricted by the HLA-B*35:01 molecule, and the APPEESFRF variant derived from an autologous HIV-1 strain induces polyfunctional responses in CD8 + T cells (2015)
ABSTRACT: Numerous reports have focused on consensus peptides to determine CD8+T-cell responses; however, few studies evaluated the functional profile using peptides derived from circulating strains of a specific region. We determined the effector profile and maturation phenotype of CD8+T-cells targeting the consensus APPEESFRS (AS9) epitope and its variant APPEESFRF (AF9), previously identified. The free energy of binding, maturation phenotype, and polyfunctional profile of both peptides were similar. The magnitude of CD8+T-cell responses toAF9 was greater than the one elicited by AS9, although the difference was not significant. The polyfunctionalprofile of AF9 was characterized by CD107a/interleukin-2 (IL-2)/macrophage inflammatory protein beta (MIP1b) and by interferon gamma (IFNc)/MIP1b/tumor necrosis factor alpha (TNFa) in response to AS9. TNFaproduction was significantly higher in response to AF9 than to AS9, and there was a negative correlation be-tween the absolute number of CD8+T-cell-producing TNFaand the plasma human immunodeficiency virus (HIV) load, suggesting a role of this cytokine in the control of HIV replication.